Standardized wild apple fruit extract as a bioactive agent in dermocosmetic products for efficacy skin hydration—In vitro and in vivo evaluation. (28th January 2022) - Stojiljković, Dragana; Nešić, Ivana; Tadić, Vanja; Najman, Stevo; Stojanović, Sanja
Abstract: Background: Wild apple fruit is rich source of bioactive substances, which can be potentially used for a production of dermocosmetic products. Aim: The aim of study was in vitro and in vivo investigation of standardized wild apple fruit extracts (obtained by purified water and maceration‐EM, percolation‐EP, Soxhlet extraction‐ES and ultrasonic extraction‐EU) and dermocosmetic creams of o/w type containing 6%, 12%, and 15% of extract EU, as extract with the best content of polyphenolic compounds (CE6, CE12, and CE15, respectively), in order to determine the optimal concentration of the extract, which manifests the best effect on the biophysical characteristics of the skin after application. Methods: Content of polyphenolic substances‐PP was investigated using HPLC analysis, while in vitro biological activity was examined on L929 fibroblasts using MTT viability test. In vivo efficacy included screening and comparison of skin hydration potential, transepidermal water loss‐TEWL, and skin pH after 28 days of creams application on healthy volunteers' skin. Results: Content of identified PP was the highest in the extract EU (2001.57 ± 0.87 mg PP/100 g EU) and satisfactory in cream CE6 (53.83 ± 0.23 mg PP/100 g CE6). Procyanidin B2 was the most common PP. Biological activity analysis showed that extract EU could be considered as non‐cytotoxic for fibroblasts in examined concentrations. In vivo investigation revealed an increase of skin hydration (after 28 days ΔEC was 21.19 ± 7.59, 26.71 ± 7.94, and 29.60 ± 10.95 for CE6, CE12, and CE15, respectively), with unchanged TEWL and skin pH values. Conclusion: Obtained results indicate that wild apple fruit extract represents a valuable source of bioactive substances, with good hydration effects of creams on human skin (effect of creams increased proportionally to the increase of concentration of incorporated extract), so it might be considered as a great potential for application in dermocosmetic industry.